Development of new alkaloid derivatives as multidrug resistance reversers in cancer cells - Vieira, Rita Mestre (2022)
Tese de mestrado, Química Medicinal e Biofarmacêutica, 2022, Universidade de Lisboa, Faculdade de Farmácia.